Photoinduced phenomena in layer-by-layer films of poly(allylamine hydrochloride) and Brilliant Yellow azodye - Zucolotto, V; Neto, NMB; Rodrigues, J. J.; Constantino, CJL; Zilio, S. C.; Mendonca, C. R.; Aroca, R. F.; Oliveira, O. N. (Amer Scientific Publishers, 2004)
The nanoscale interactions between adjacent layers of layer-by-layer (LBL) films from poly(allylamine hydrochloride) (PAH) and azodye Brilliant Yellow (BY) have been investigated, with the films employed for optical storage and the formation of surface-relief gratings. Using Fourier transform infrared spectroscopy, we identified interactions involving SO3- groups from BY and NH3+ groups from PAH. These electrostatic interactions were responsible for the slow kinetics of writing in the optical storage experiments, due to a tendency to hinder photoisomerization and the subsequent reorientation of the azochromophores. The photoinduced birefringence did not saturate after one hour of exposure to the writing laser, whereas in azopolymer films, saturation is normally reached within a few minutes. on the other hand, the presence of such interactions prevented thermal relaxation of the chromophores after the writing laser was switched off, leading to a very stable written pattern. Moreover, the nanoscale interactions promoted mass transport for photoinscription of surface-relief gratings on PAH/BY LBL films, with the azochromophores being able to drag the inert PAH chains when undergoing the trans-cis-trans photoisomerization cycles. A low level of chromophore degradation was involved in the SRG photoinscription, which was confirmed with micro-Raman and fluorescence spectroscopies.
Keywords: layer-by-layer films; poly(allylamine hydrochloride); Brilliant Yellow azodye; photo-induced phenomena; optical storage; Raman spectroscopy; fluorescence spectroscopy